RUSSIAN FOREIGN POLICY TOWARD WESTERN EUROPE: COMPARATIVE STUDIES BETWEEN BORIS YELTSIN AND VLADIMIR PUTIN - Savira Rahmawati (HI 15 UMY 461, 2015)
*461 This thesis interpreted the Russian Foreign Policy under president Vladimir Putin. The collapse of Soviet Union confronts Russia on the agenda changes are layered. Russia must adjust the political system, the economic system and search for a new orientation role in the international arena. In the context of foreign policy, Russia is required to create a foreign policy that supports political and economical changes in the country and adapt to changes in the international environment. Leaders substitution also affect the change of direction and strategy of Russia's foreign policy. As Russia's first president after the collapse of the Soviet Union, Boris Yeltsin sought to realize "New Revolution of Russia", and tried to bring Russia on a new era that was different from the previous era. Yeltsin also trying to expand this influence in the countries of the former Soviet Union and is open to cooperate with other countries for the progress of the Russian economy. Under Yeltsin's leadership, Russia tried to establish a close relationship with western countries for example with Russia joining the World Trade Organization or WTO dominated by western countries. Through the "new revolution of Russia", Russian suddenly entered a new era that was too much different from the previous era, although Yeltsin showed several times to confirm the power of authoritarian attitude as greater latitude in when the communist era. In May 2000, Vladimir Putin replaced Boris Yeltsin as president of Russia. In essence Vladimir Putin inherited traces of the leader of its predecessor, Boris Yeltsin continuing reforms and the free market. But Putin has the attitude and the different ways of implementing it, he is reviewing the causes deterioration of the country, one of which is the development of oligarchs in Russia. The main focus of Putin is cracking down on the oligarchs and eradicating sometimes undemocratic way was doing. Vladimir Putin revise the concept of Boris Yeltsin's foreign policy ever enacted in 1993. The new concept was passed on June 28, 2000 further confirms Putin's vision, mission and strategy of political and foreign policy of the Russian Federation. This concept also served as guidelines for the formulation of foreign policy and Russia's actions in a world system which had undergone changes that ultimately Putin firmly decided to move away from the west. Russian foreign policy differences althraeted authors to discuss during the reign of era Yeltsin and Putin talked about his approach and moved away from the west. The theme entitled " Russian Foreign Policy Toward Western Europe Comparative Studies Between Boris Yeltsin And Vladimir Putinâ€.